Pemenuhan Hak-Hak Khusus Pekerja Perempuan Di Kabupaten Karanganyar Berdasarkan UU No 13 Tahun 2003 Tentang Ketenagakerjaan - Juli Setyo Rini; Purwono Sungkowo Raharjo (Amal Insani Foundation, 2023)
This research describes and examines the problems regarding the fulfillment of the special rights of women workers in 2 companies, namely PT Argantha Jaya Globalindo and PT Menara Kartika Buana. The first problem is how to fulfill the special rights of women workers and the obstacles to fulfilling the special rights of women workers. This research is an empirical normative legal research that is prescriptive and applied. The sources of law used are primary and secondary sources of law. Data collection techniques, namely literature study and interviews, interviews were conducted with female workers at PT Argantha Jaya Globalindo and PT Menara Kartika Buana as well as from the Surakarta animal workers' labor inspector. The analysis technique used is the syllogistic method which uses a deductive mindset. The results of the discussion explained that, first, the fulfillment of the special rights of women workers at PT Argantha and PT Manara had not been properly fulfilled, there were still violations, especially in fulfilling salaries when taking leave. Second, there are obstacles in fulfilling the rights of women workers from animal workers, companies and women workers.